Large-scale agricultural land investments and food security in Nigeria - Oluwatosin D. Edafe; Evans Osabuohien; Oluwatoyin Matthew; Isaiah Olurinola; Joel Edafe; Romanus Osabohien (Heliyon, 2023)
The study examines how large-scale agricultural land investments (LIs) affect household food security in Nigeria. It is one of the few studies in Nigeria that offers new empirical insights into household food security. Precisely, it unravels how LIs affect the livelihood outcomes of households in communities where LIs operate compared to households in communities without such LIs. This study engages the mixed methods of analysis involving quantitative and qualitative techniques. The quantitative data is drawn from the Living Standards Measurement Study-Integrated Surveys on Agriculture (LSMS-ISA) utilising the Logistic regression technique. The qualitative aspect of this study involved fieldwork conducted in two distinct Nigerian states: Kwara State, situated in the North-Central region, and Ogun State, located in the South-West region. The qualitative findings further enrich the quantitative findings. It also helped to investigate the nature of jobs households engaged in and also the employment density of the investors’ farms which could not be done using the national representative data (LSMS). The results indicate that households in communities without land investments have 0.2% higher likelihood of being more food secure than households in communities with land investments and it is significant at 5%. The qualitative analysis reveals several key insights, including the observation that female headed households in communities with LIs are less likely to be food secure, receive less wages, and spend more time in communities with LIs. Government should put in place policies (for example, compensation policies) that will ensure that land deals are properly monitored and structured to benefit and protect the host communities. If the government fails to properly regulate land deals, rural people will always suffer. Also, they should monitor and control the activities, and the type of crops grown in investment farms so that land investments can bring about the desired benefits such as improvement in household livelihood and enhance food security in the communities where they exist.